(untitled) (Research, Society and Development, 2025)
This study aims to analyze the practice of sedation in Rapid Sequence Intubation (RSI) in pediatric patients, highlighting its importance in ensuring safety and efficacy during the procedure. RSI is widely used in pediatrics as a method to facilitate orotracheal intubation, being fundamental in minimizing severe complications such as hypoxia, aspiration, and hemodynamic instability. The methodology adopted consists of a bibliographic review of scientific articles published between 2018 and 2023, focusing on international guidelines and updated clinical evidence. The results demonstrate that the careful selection of sedative agents and neuromuscular blockers plays an essential role in ensuring procedural efficacy and reducing associated risks. Additionally, adequate team preparation, continuous patient monitoring, and strict adherence to established protocols are determining factors for safety and clinical success. It is concluded that the careful application of RSI in pediatrics requires specialized training and an interdisciplinary approach, promoting safe, effective, and humanized care tailored to the specific needs of the pediatric population.